Recent advances in catalysis using transition metals-bounding organic ligands assisted by ultrasound and/or microwave - Álvarez, Mónica Beatriz (2015)
Usually, in organic and organometallic synthesis an external conventional heat source is applied to carry out a chemical reaction at high temperature. Nonetheless, these conventional heating systems have some disadvantages as the heterogeneous heating causing a low reproducibility of the results and extended reaction times. A promising alternative is the use of microwave (MW) and ultrasound (US) energy. The use of these techniques has led to considerable advantages as better homogeneity in temperature and very short reaction time. By virtue of the effects mentioned above, the MW and US irradiation constitutes a convenient way to accelerate and improve a great number of organic and organometallic reactions. In this paper, we have compiled an overview developed during the last decade in the synthesis of such catalysts and organic transformations assisted by both techniques mentioned above.